Unlocking public service potential: The impact of competency and career development on local government performance in emerging economies - Tammubua, Milcha Handayani; Warokka, Ari; Aqmar, Aina Zatil (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates key determinants of civil servant performance in local governments of emerging economies, with a particular focus on Papua Province, Indonesia. It specifically evaluates how competence, job placement, and career development contribute to performance outcomes and explores the moderating roles of education level and job tenure. A quantitative research design was employed, using a structured questionnaire to gather data from 325 local public officers. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (PLS-MGA) to test direct and moderating effects. The results reveal that both competence and career development significantly enhance employee performance, while job placement does not exhibit a notable impact. Furthermore, education level positively moderates the relationship between competence and performance, and job tenure strengthens the effect of career development on performance. Competency-building and strategic career development initiatives are critical for optimizing civil servant performance. These interventions are most effective when aligned with individual educational backgrounds and job tenure levels. The findings underscore the need for context-specific HRM strategies in remote or underperforming regions. Policymakers and administrators should prioritize structured training programs and tailored career development frameworks to bolster public sector performance in emerging regions.